Cross-Border Cooperation as Part of the Irish Peace Process: Opportunities, Impacts And Challenges - Andy Pollak (Central European Public Administration Review)
Cross-border cooperation between Northern Ireland and the Republic of Ireland emerging out of the 1968–1998 conflict is an important and largely successful dimension of the peace process in Ireland, with institutional cooperation between the two governments on the island playing a key role. This article looks at the level of interaction between North and South on the island; asks what role the EU has played in this process and what are the challenges of measuring the impact of such cooperation; outlines the work of the Centre for Cross Border Studies, and looks ahead to the challenges facing cross-border cooperation in a period of severe financial and economic constraints.